2020
DOI: 10.1186/s13287-020-01626-6
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical tissue recovery in severe congenital obstructive hydrocephalus after intraventricular administration of bone marrow-derived mesenchymal stem cells

Abstract: Background: In obstructive congenital hydrocephalus, cerebrospinal fluid accumulation is associated with high intracranial pressure and the presence of periventricular edema, ischemia/hypoxia, damage of the white matter, and glial reactions in the neocortex. The viability and short time effects of a therapy based on bone marrow-derived mesenchymal stem cells (BM-MSC) have been evaluated in such pathological conditions in the hyh mouse model. Methods: BM-MSC obtained from mice expressing fluorescent mRFP1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…The expression of some stem cell markers was studied to confirm that BM-MSCs did not transdifferentiate after transplantation. Transplanted BM-MSCs maintained the expression of nestin (detected with the antibody Rat-401), NG2, βIII-tubulin, δGFAP, and αGFAP ( Figure 1 d–h) in the same way as they did in vitro (for details, see [ 17 ]) indicating no transdifferentiation. NG2, βIII-tubulin, and αGFAP immunoreactions in the transplanted BM-MSCs were weak compared to the corresponding labeling in oligodendrocyte progenitors, neuroblasts, or astrocytes, respectively.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The expression of some stem cell markers was studied to confirm that BM-MSCs did not transdifferentiate after transplantation. Transplanted BM-MSCs maintained the expression of nestin (detected with the antibody Rat-401), NG2, βIII-tubulin, δGFAP, and αGFAP ( Figure 1 d–h) in the same way as they did in vitro (for details, see [ 17 ]) indicating no transdifferentiation. NG2, βIII-tubulin, and αGFAP immunoreactions in the transplanted BM-MSCs were weak compared to the corresponding labeling in oligodendrocyte progenitors, neuroblasts, or astrocytes, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…Various stem cell therapies have been assayed in experimental forms of congenital and acquired feto-neonatal hydrocephalus. Neural stem cells [ 15 ] and mesenchymal stem cells [ 16 , 17 ] have shown promising results in hydrocephalus of obstructive and posthemorrhagic origins. In neurodegenerative diseases, bone marrow-derived mesenchymal stem cells (BM-MSCs) were shown to play a neuroprotective role due to their capacity to migrate to degenerated regions and produce different growth factors [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent studies in 2013 and 2015, it was found that implantation of mesenchymal stem cells (MSCs) in the ventricular wall resulted in the prevention of the progression of hydrocephalus as well as the neurorepair of the injured site [ 69 , 108 ]. An additional study in 2020 confirmed that MSC implantation in the ventricular wall resulted in a decrease in inflammation, and an increase in neurorepair which rescued the neurodegeneration due to hydrocephalus [ 109 ]. Additionally, in 2018 a Phase I clinical trial was completed which evaluated the safety and tolerability of MSC grafts in pediatric hydrocephalus patients.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is not probable that such notable changes in phosphatidylserine levels detected in the present study were implied in apoptosis. We have previously shown that the apoptosis rate in the neocortical grey matter of the hyh mice is low, non-detectable [ 61 ]. Thus, apoptosis only can be detected in the periventricular white matter of hyh mice.…”
Section: Discussionmentioning
confidence: 99%